EFFECT OF COMPENSATION ON EMPLOYEE SATISFACTION AND EMPLOYEE PERFORMANCE - Anton Saman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the effect of compensation on job satisfaction and the effect of compensation on employee performance in the Mining Company. Data collected by interview, observation and literature study. The study is conducted against 51 employees with analisist the data using methods Partial Least Square (PLS). The results of this study reveal that compensation has a significant effect on job satisfaction, in addition, compensation also has a significant effect on employee performance. Keyword: Compensation, satisfaction of work, the performance of employee